BIOMETRY AND EMERGENCE Amburana cearensis (Allemão) A.C.Smith ACCORDING TO THE FRUIT COLOR - Giovana Lopes da Silva; Sebastião Medeiros Filho; Roberta Boscaini Zandavalli; Diego de Sousa Pereira; Geocleber Gomes de Sousa (Ciência Florestal, 2013)
http://dx.doi.org/10.5902/1980509812347 This paper evaluated the biometry of fruits, seeds and seedling emergence of Amburana cearensis (Allemão)AC Smith derived from fruits with different stages of coloring and drying. Fruits of red color, dark andclosed and the ground seeds were collected after dehiscence of the fruit. At each stage of maturation, length,width and thickness of fruits and seeds were measured. Then, we proceeded to the descriptive analysis.To test the emergency four replicates of 25 seeds were seeded and distributed in a completely randomizeddesign with factorial [(2 x 2 + 1)] and two fruit colors (red and dark) and two drying conditions (with andwithout ) and an additional (seeds collected on the ground after dehiscence). The evaluation was done bydetermining: the percentage, index of speed and average time of emergency, and measuring the height andshoot dry matter of the seedling. Considering the results, it was found that red and black fruits and theirseeds of Amburana cearensis have different biometric characteristics and the drying process favors theemergence percentage, but had no positive effect on height and shoot dry matter.